The European Court of Human Rights: Procedural and Jurisprudential Framework - Krajnyák, Enikő (The European Convention on Human Rights: A Central and Eastern European Perspective, 2026)
This chapter examines the role and functioning of the European Court of Human Rights (ECtHR) with a focus on its institutional structure, procedural framework, and the main interpretative doctrines shaping its jurisprudence. It explores how the Court adjudicates individual and inter-State applications and develops the standards of the European Convention on Human Rights (ECHR) in response to contemporary legal challenges. It also examines key interpretative doctrines, including the margin of appreciation and the living instrument doctrines, which illustrate the Court’s dynamic interpretative approach and its effort to balance evolution with respect for State sovereignty and democratic legitimacy. Keywords: ECtHR, human rights, procedure, margin of appreciation, living instrument doctrine, jurisprudence